Whose Wall is it Anyway? Using street art to navigate the private and the public in a community. - Augusto Rodrigues, Anna (Street Art & Urban Creativity, 2020)
In this working paper, I investigate the tensions and questions that arise when street artists use private walls in communities to create their work. I will also discuss how street art complicates, at times, traditional understandings of private and public spaces in neighbourhoods. Written in the style of academic journalism, this working paper is an attempt to work through questions that surface from trying to understand the impact street art, when positioned as public pedagogy, may have on those who live and create in a community.